Strategic Branding in the Digital Age: Optimizing Pesantren Broadcasting Media for Institutional Image - Hidayah, Luthfi; Alhifni, Anas; Ilham, Moch Khoirul (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
The development of religious institution-based broadcasting media has opened a strategic space for Islamic boarding schools (pondok pesantren) to build their institutional image within society. Radio and TV Persada of Sunan Drajat Islamic Boarding School in Lamongan serve as da'wah media and mass communication tools that play a significant role in shaping public perception regarding the existence and values of the pesantren. This study aims to analyze the role of Radio and TV Persada in shaping the image of the Sunan Drajat Lamongan Islamic Boarding School and to identify the supporting and inhibiting factors in its implementation. This study uses a qualitative case-study approach. Data collection techniques included in-depth interviews with media managers, Islamic boarding school leaders, and listeners/viewers, observation of broadcast content, and documentation of Persada Radio and TV programs. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The analytical framework of this study draws on mass communication theory, specifically uses and gratifications theory, to understand how media messages are constructed and received by audiences. The results show that radio and television play an important role in building a positive image of Islamic boarding schools by consistently broadcasting religious, educational, and institutional information relevant to community needs. Consistency of messages, credibility of preachers and Islamic boarding school leaders, and the media's proximity to the community are key factors in strengthening the institution's image. That said, limitations in human resources, broadcasting technology, and broadcast coverage remain challenges to optimizing the media's role. This study is expected to contribute theoretically to the development of studies on da'wah communication and pesantren media, as well as practically to pesantren broadcasting media managers in designing effective communication strategies to build a sustainable institutional image.